2021
DOI: 10.3389/fcell.2021.671067
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between SUMO and Ubiquitin-Like Proteins: Implication for Antiviral Defense

Abstract: Interferon (IFN) is a crucial first line of defense against viral infection. This cytokine induces the expression of several IFN-Stimulated Genes (ISGs), some of which act as restriction factors. Upon IFN stimulation, cells also express ISG15 and SUMO, two key ubiquitin-like (Ubl) modifiers that play important roles in the antiviral response. IFN itself increases the global cellular SUMOylation in a PML-dependent manner. Mass spectrometry-based proteomics enables the large-scale identification of Ubl protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 238 publications
0
19
0
Order By: Relevance
“…It has been reported that SUMOylation are closely related to cancer initiation and progression ( Xie et al, 2020 ). There is a crosstalk between ubiquitination and SUMOylation in cells ( Chelbi-Alix and Thibault, 2021 ), and SUMOylation plays a significant role in maintaining genomic stability via SUMO-targeted ubiquitin ligase (STUbL) ( Nie and Boddy, 2016 ). Interestingly, we also found a significant change of ubiquitination pathway when we performed KEGG enrichment analysis of all down-regulated phosphorylation in CRC cells versus the normal cells ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that SUMOylation are closely related to cancer initiation and progression ( Xie et al, 2020 ). There is a crosstalk between ubiquitination and SUMOylation in cells ( Chelbi-Alix and Thibault, 2021 ), and SUMOylation plays a significant role in maintaining genomic stability via SUMO-targeted ubiquitin ligase (STUbL) ( Nie and Boddy, 2016 ). Interestingly, we also found a significant change of ubiquitination pathway when we performed KEGG enrichment analysis of all down-regulated phosphorylation in CRC cells versus the normal cells ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms have been demonstrated through which free ISG15 and ISGylation possibly contribute to the etiology of human ailments. ISG15 is involved through marking proteins for degradation, antagonizing protein degradation (stabilizing proteins), affecting protein localization, preventing the formation of protein complexes, or regulating immune response(s) [96,126,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. In the current review, we shall focus on the role of the ISG15 pathway in human diseases through protein degradation.…”
Section: The Isg15 Pathway In Human Diseasesmentioning
confidence: 99%
“…[ 124 ] SUMOylation also plays an important role downstream of IFN antiviral defense, which has recently been the focus of a large amount of work. [ 125 , 126 ]…”
Section: Sumoylation Is a Vital Regulator Of Antiviral Innate And Int...mentioning
confidence: 99%